Money laundering, cybercrime and criminal responsibility of legal persons - Souto, Miguel Abel (2019)
Directives 2015/849, and 2018/843 on Money Laundering require continuous adaptations of the legal framework to respond to threats of the use of new technologies in money laundering. Directive 2018/843 extends the scope of Directive 2015/849 to providers engaged in exchange services between virtual currencies and fiat currencies as well as custodian wallet providers. Undoubtedly, the new payment systems facilitate money launderers’ criminal activity. These systems are better than cash for moving large sums of money, non-face to face business relationships favour the use of straw buyers, and false identities, the absence of credit risk, as there is usually a prepaid payment, discourages service providers from obtaining a complete, and accurate customer information, and the nature of the trade, and the speed of transactions make it difficult to control property or freezing. However, the development of technologies, including the internet, has unquestionable advantages involved and even provides, through online resources, verification of identity, or other duty of surveillance, for the prevention of money laundering. In addition, the reform of June 22, 2010 introduced in Spain the criminal liability of legal persons, and incorporated money laundering together with other crimes to this innovative model of criminal responsibility. Soon after, Organic Law 1/2015, of March 30, modified the hereto barely applied regulation. Itis quite surprising that Organic Law 1/2015 boasts of making a technical improvement, as it incurs obvious contradictions by exempting criminal liability to legal persons for a money laundering, that should not have existed due to the adoptionand effective execution of suitable or adequate compliance programs to prevent it, as well as taking into account to limit the punishment non-serious breaches of supervisory, monitoring, and control duties, when letter b) of the first paragraph of article 31 bis only takes into consideration serious breaches of those duties. Already in 2010, in order to introduce the criminal liability of legal persons, the Spanish Legislator invoked the alleged need to comply with international commitments. However, this model of responsibility was not mandatory, because international agreements normally only require effective, proportionate, and dissuasive sanctions. In addition, managers and executives, who have not adopted an effective compliance program, will be held liable together with the company, given that now all act as police officers. In conclusion, the use of dummy corporations for money laundering is frequent, as it is evidenced by the judgments of theSupreme Court of June 26, 2012, and February 4, 2015, but until recently, the accessory consequences and the doctrine of piercing the corporate veil were sufficient.